(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Acute liver failure is defined as a severe acute liver injury for lesser than 26 [3] weeks duration with encephalopathy and impaired synthetic function in a patient without cirrhosis or preexisting liver disease. It is associated with morbidity and mortality and its overall survival rate has improved through intensive care management and advancements [1,2] in liver transplants. Etiologies vary by age with metabolic and infectious diseases prominent in the first year of life and acetaminophen overdose and Wilson’s disease occurring in adolescents. IAP definition: liver dysfunction within 8 weeks of onset of symptoms (neonates may have deranged liver functions without overt symptoms) which is uncorrectable (6-8 hours after administration of one dose of parenteral vitamin K) coagulopathy with INR >1.5 with hepatic encephalopathy or INR >2.0 in patients without encephalopathy and no evidence of chronic liver disease either at presentation or in the past.